Aliveness and the off-switch in human-robot relations - Sandry, Eleanor (Peter Lang, 2018)
If robots are going to share human homes, workplaces and social spaces in the future, how will they communicate with people, and how might this frame people’s perceptions of them? Should a robot’s communication style reinforce the sense in which they seem to be somewhat alive, trustworthy assistants, co-workers or possibly even friends? Is there value in people recognizing and respecting the agency of robots, while also being reminded that even the most personable social robot is a machine that can be switched off? The questions in this list are too complex to answer fully in this short chapter. Its aim, instead, is to offer a starting point for discussing such questions: to demonstrate how a detailed analysis of people’s communication with and about robots from a number of communication theoretical perspectives is a productive way to think through the deployment of robots into everyday life.